2022
DOI: 10.3390/s22218200
|View full text |Cite
|
Sign up to set email alerts
|

Development of Online Tool Wear-Out Detection System Using Silver–Polyester Thick Film Sensor for Low-Duty Cycle Machining Operations

Abstract: This paper deals with the design and development of a silver–polyester thick film sensor and associated system for the wear-out detection of single-point cutting tools for low-duty cycle machining operations. Conventional means of wear-out detection use dynamometers, accelerometers, microphones, acoustic emission sensors, thermal infrared cameras, and machine vision systems that detect tool wear during the process. Direct measurements with optical instruments are accurate but affect the machining process. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Therefore, the use of sensors for realtime monitoring of the cutting process of cutting force, cutting temperature, cutting vibration, and other physical signals, the purpose of which is to ensure the parts meet the standards of qualification, to avoid excessive wear or the tool, resulting in unnecessary waste. Rakkiyannan et al [101] installed a thick silver polyester film sensor directly at the tip of the cutting tool, allowing wear to act directly on the sensor to monitor the real-time status of the tool under low loads. In addition to the above monitoring of typical physical quantities in the cutting process, there are a variety of methods for online monitoring of tool wear, including optical monitoring, audio monitoring, AE technology, spindle motor current/power monitoring, and ultrasonic monitoring which are also methods of indirectly monitoring the state of tool wear using sensors.…”
Section: Tool Wear Online Monitoring Technologymentioning
confidence: 99%
“…Therefore, the use of sensors for realtime monitoring of the cutting process of cutting force, cutting temperature, cutting vibration, and other physical signals, the purpose of which is to ensure the parts meet the standards of qualification, to avoid excessive wear or the tool, resulting in unnecessary waste. Rakkiyannan et al [101] installed a thick silver polyester film sensor directly at the tip of the cutting tool, allowing wear to act directly on the sensor to monitor the real-time status of the tool under low loads. In addition to the above monitoring of typical physical quantities in the cutting process, there are a variety of methods for online monitoring of tool wear, including optical monitoring, audio monitoring, AE technology, spindle motor current/power monitoring, and ultrasonic monitoring which are also methods of indirectly monitoring the state of tool wear using sensors.…”
Section: Tool Wear Online Monitoring Technologymentioning
confidence: 99%
“…Another variable used is temperature; in the work presented by Rakkiyannan et al [10], a sensor was designed and placed on a high-speed steel cutting tool and the changes in temperature and deformation provided information on the state of the tool while cutting mild steel. The results were corroborated with thermographic images, and three levels were successfully detected with a span of 1.2 mm due to the sensor's degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Several literature reviews have identified the main techniques, tools and trends for processing [21][22][23][24]. Firstly, signals are processed directly in the time domain [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] or techniques or transforms are used for their analyses in the frequency [3,5,[18][19][20] or time-frequency [19,20] domains. From here, several techniques are used to obtain features that allow the analysis to be carried out in a better way, such as the use of statistical indicators [3][4][5][6]8,14,[18][19][20], time or time-frequency transforms for direct feature extraction [3][4][5]19,20] and, in some cases, methods for the selection of the most appropriate features or dimensionality reduction such as heuristic techniques [5,6,22], linear discriminant analysis (LDA) [19] or principal component analysis (PCA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation